Feature analysis aided design of lightweight heat sink from network structures - Tianlin Luo; Changliang Zhu; Baowen Li; Xiangying Shen; Guimei Zhu (iScience)
Summary: The advent of electronic devices has revolutionized engineering applications and fundamentally transformed society. However, their lifespan is significantly impacted by operational temperatures, as excess heat can elevate localized temperatures (hot spot) and damage components. Efficient heat dissipation through heat sinks is therefore crucial. In this research, we optimized intricate network structures for designing heat sink fins. These novel configurations provide thermal dissipation capabilities equivalent to conventional designs while substantially reducing weight. We utilized 3D printing to manufacture these designs and confirmed their effectiveness through experimental validation. The optimized network-based heat sink designs exhibit a weight reduction of approximately 50% while maintaining cooling efficiency comparable to commercially available models. Additionally, we introduced the “effective heat transfer coefficient heff” to assess heat dissipation effectiveness. This factor considers temperature fluctuations under thermal loads and the heat sink’s surface area. The refined heat sink designs were successfully implemented to cool light emitting diodes (LEDs） in practical applications.